Turning RuBisCO-enriched snap pea protein concentrates into function: A novel plant protein for fat-free whipped cream alternatives - Qinghao Ning; Jordy Kim Ung Ling; Jia Yee Wu; Tamilvendan Manavalan; Gomathy Sandhya Subramanian; Nurhidayah Basri; Yin Win Khin; Yoganathan Kanagasundaram; Jayantha Gunaratne; Maria N. Antipina; Siew Bee Ng (Food Hydrocolloids, 2026)

Tailoring chickpea protein functionality for food applications through supercritical CO2 processing - Gomathy Sandhya Subramanian; Daryl Lee; Su Hui Lim; Sergey Gorelik; Celyne Halim; Ashley Lim; Shi Jie Ang; Dylan Hao Wen Swee; Uma Jingxin Tay; Sreenivasa Reddy Puniredd; Khin Yin Win; Yoganathan Kanagasundaram; et al. (Food Research International, 2025)

A new lignicolous fungus, Rhexoacrodictys chiangraiensis ( Pleurotheciales, Ascomycota ), from Northern Thailand - Hsan Win; Chitrabhanu S. Bhunjun; Sajeewa S. N. Maharachchikumbura (New Zealand Journal of Botany, 2025)

Semi-synthesis of phenolic-amides and their cytotoxicity against THP-1, HeLa, HepG2 and MCF-7 cell lines - Jaggaiah N. Gorantla; Sunaree Choknud; Eko Suyanto; Htun-Htun Win; Yanling Hua; Maniganda Santhi; Sirilak Wangngae; Anyanee Kamkaew; Mariena Ketudat-Cairns; Lalida Rojanathammanee; James R. Ketudat Cairns (Natural Product Research, 2024)

Online citizen science with the Zooniverse for analysis of biological volumetric data - Patricia Smith; Oliver N. F. King; Avery Pennington; Win Tun; Mark Basham; Martin L. Jones; Lucy M. Collinson; Michele C. Darrow; Helen Spiers (Histochemistry and Cell Biology, 2023)
Public participation in research, also known as citizen science, is being increasingly adopted for the analysis of biological volumetric data. Researchers working in this domain are applying online citizen science as a scalable distributed data analysis approach, with recent research demonstrating that non-experts can productively contribute to tasks such as the segmentation of organelles in volume electron microscopy data. This, alongside the growing challenge to rapidly process the large amounts of biological volumetric data now routinely produced, means there is increasing interest within the research community to apply online citizen science for the analysis of data in this context. Here, we synthesise core methodological principles and practices for applying citizen science for analysis of biological volumetric data. We collate and share the knowledge and experience of multiple research teams who have applied online citizen science for the analysis of volumetric biological data using the Zooniverse platform ( www.zooniverse.org ). We hope this provides inspiration and practical guidance regarding how contributor effort via online citizen science may be usefully applied in this domain.

How context affects transdisciplinary research: insights from Asia, Africa and Latin America - Flurina Schneider; Aymara Llanque-Zonta; Onintsoa Ravaka Andriamihaja; R. Ntsiva N. Andriatsitohaina; Aung Myin Tun; Kiteme Boniface; Johanna Jacobi; Enrico Celio; Clara Léonie Diebold; Laby Patrick; Phokham Latthachack; Jorge Claudio Llopis; et al. (Sustainability Science, 2022)
Transdisciplinary research (TDR) has been developed to generate knowledge that effectively fosters the capabilities of various societal actors to realize sustainability transformations. The development of TDR theories, principles, and methods has been largely governed by researchers from the global North and has reflected their contextual conditions. To enable more context-sensitive TDR framing, we sought to identify which contextual characteristics affect the design and implementation of TDR in six case studies in Asia, Latin America, and Africa, and what this means for TDR as a scientific approach. To this end, we distinguished four TDR process elements and identified several associated context dimensions that appeared to influence them. Our analysis showed that contextual characteristics prevalent in many Southern research sites—such as highly volatile socio-political situations and relatively weak support infrastructure—can make TDR a challenging endeavour. However, we also observed a high degree of variation in the contextual characteristics of our sites in the global South, including regarding group deliberation, research freedom, and dominant perceptions of the appropriate relationship between science, society, and policy. We argue that TDR in these contexts requires pragmatic adaptations as well as more fundamental reflection on underlying epistemological concepts around what it means to conduct “good science”, as certain contextual characteristics may influence core epistemological values of TDR.

Total Dental Occlusal Area as a Feeding Constraint Feature in Extant Walruses (Odobenus rosmarus), and Implications for the Evolution of Molluscivory in Odobenidae - Win N. F. McLaughlin; Caitlyn J. Boatman; Edward B. Davis; Samantha S. B. Hopkins (Journal of Mammalian Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

High prevalence of mismatch repair deficiency in prostate cancers diagnosed in mismatch repair gene mutation carriers from the colon cancer family registry - Christophe Rosty; Michael D. Walsh; Noralane M. Lindor; Stephen N. Thibodeau; Erin Mundt; Steven Gallinger; Melyssa Aronson; Aaron Pollett; John A. Baron; Sally Pearson; Mark Clendenning; Rhiannon J. Walters; et al. (Familial Cancer, 2014)